IMPLEMENTASI METODE FUN LEARNING SEBAGAI INOVASI PEMBELAJARAN ABAD 21 DALAM MENINGKATKAN KEAKTIFAN PESERTA DIDIK - Susan Nurwidianing; Deri Hendriawan; Sardin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
21st-century learning demands innovative learning methods that can increase student engagement in the learning process. One approach relevant to these demands is the fun learning method, a learning method that emphasizes a fun, interactive, and student-centered learning atmosphere. This study aims to describe the implementation of the fun learning method as a 21st-century learning innovation in increasing student engagement. This study uses a qualitative approach with students and teachers at the elementary education level as research subjects. This study uses a qualitative method that involves an in-depth understanding of the phenomena being studied by examining each case in detail. The nature of the problems being studied can vary, and to ensure the success of qualitative research, accurate and complete data collection is required, both in the form of primary data and secondary data. The research results show that the implementation of the fun learning method can create a more engaging learning atmosphere, increase active student participation, and encourage their involvement in asking questions, discussing, and collaborating during the learning process. Furthermore, this method also helps teachers develop creative and innovative learning in accordance with the characteristics of 21st-century learning. Thus, it can be concluded that the fun learning method is an effective learning innovation in increasing student activeness and supporting the achievement of 21st-century learning objectives.